2015
DOI: 10.4238/2015.april.28.4
|View full text |Cite
|
Sign up to set email alerts
|

Structural modeling and analysis of dengue-mediated inhibition of interferon signaling pathway

Abstract: ABSTRACT. Dengue virus (DENV) belongs to the family Flaviviridae and can cause major health problems worldwide, including dengue fever and dengue shock syndrome. DENV replicon in human cells inhibits interferon α and β with the help of its non-structural proteins. Nonstructural protein 5 (NS5) of DENV is responsible for the proteasomemediated degradation of signal transducer and activator of transcription B. Aslam et al. 4216©FUNPEC-RP www.funpecrp.com.br Genetics and Molecular Research 14 (2): 4215-4237 (2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 72 publications
1
4
0
Order By: Relevance
“…Disruption of these interactions abrogated NS5-mediated hSTAT2 degradation, interferon suppression, and viral infection. These results are also in agreement with previous demonstration that the difference in NS5-mediated binding and degradation between hSTAT2 (NS5-sensitive) and mSTAT2 (NS5-resistant) maps largely to the coiled-coil domain [ 85 ]. Very recently, the coiled-coil domain was also shown to be necessary and sufficient for STAT2 degradation by ZIKV NS5 [ 86 ], suggesting conservation of this mechanism between these two flavivurses.…”
Section: Stat2 Degradation By the Ubiquitin–proteasome System (Ups)supporting
confidence: 93%
“…Disruption of these interactions abrogated NS5-mediated hSTAT2 degradation, interferon suppression, and viral infection. These results are also in agreement with previous demonstration that the difference in NS5-mediated binding and degradation between hSTAT2 (NS5-sensitive) and mSTAT2 (NS5-resistant) maps largely to the coiled-coil domain [ 85 ]. Very recently, the coiled-coil domain was also shown to be necessary and sufficient for STAT2 degradation by ZIKV NS5 [ 86 ], suggesting conservation of this mechanism between these two flavivurses.…”
Section: Stat2 Degradation By the Ubiquitin–proteasome System (Ups)supporting
confidence: 93%
“…These factors encompass inhibitors of dsRNA sensors 171,172 and their transducers 173 , dsDNA sensors 174 and their transducers [175][176][177][178] and the transcription factors executing the cellular response to foreign nucleic acids, including IRF3 and IRF7 (refs. 176,177,[179][180][181][182] ). Along similar lines, cancer cells harness strategies to limit nucleic-acid-driven innate immune signaling in support of immunoevasion.…”
Section: Subversion Of Icd By Viruses and Cancer Cellsmentioning
confidence: 99%
“…Many researchers had found that NSs of different viruses played important role in blocking interferon-mediated antiviral effect. One report found that non-structure protein 5 (NS5) of Dengue virus (DENV) interacted with STAT2 to block IFN signaling pathway[ 16 ]. Another research claimed that NS5A protein of Hepatitis C Virus (HCV) could disrupt STAT1 phosphorylation and suppressed Type I interferon signaling[ 17 ].…”
Section: Introductionmentioning
confidence: 99%